4 Agrochemical Residues, Product Quality, and Safety of Beef Fed Cotton Ginning and Other Byproduct Feeds. (28th November 2020) - Smith, David J
Abstract: Most commodity crops undergo milling, husking, ginning or other processing procedures before use as human food or fiber. Byproduct nutrient density varies with the type of grain or oil seed processed and use typically varies with nutrient needs of specific production situations. Drought or high grain prices may increase the use of byproducts; regionally available, low-cost ingredients such as cotton ginning byproduct may be used extensively by beef producers to replace forage. Doubt associated with the use of such byproducts is not typically related to nutritional value but with uncertainties about the presence of residual pesticides, herbicides, or harvest-aid chemicals. Potential chemical residues in consumer products and the concomitant financial and reputational losses borne by the industry provide an impetus for concern. Negative experiences with contaminated Australian beef established a long-lived suspicion of "cotton trash" that continues to impact the industry today. The purpose of this review is to discuss sources, amounts, and risks of chemical residues associated with byproduct feeds used in the southern United States with cotton ginning byproducts as a major focus. The use patterns of specific crop protection and harvest-aid chemicals will be discussed in context with chemical tolerances established by the U.S. EPA. In addition, U.S. pesticide monitoring programs in beef will be discussed. Although data describing the transmission of chemical residues from byproduct feeds into beef products are limited, the available data suggest some best practices could be adopted to mitigate concerns and minimize possible agrochemical residue contamination of beef.